Description Of The Implementation Of Acupressure Therapy Against Dysmenorrhea Pain In Adolescent Girls At SMKN 1 Ciamis - Rika Rosanti; Ririn Lestari; Arifah Septiane Mukti; Ratna Suminar (Universitas Galuh, 2025)
The prevalence of dysmenorrhea, ranging from mild to severe, in Indonesia stands at 74.1%. Approximately 50% of women who menstruate suffer from dysmenorrhea, with 10% experiencing symptoms severe enough to necessitate rest, and only 1% to 2% seeking care at a health center. Among adolescent girls, the discomfort associated with menstrual pain often hinders concentration during learning activities. Dysmenorrhea can be managed through both pharmacological and non-pharmacological methods, with acupressure therapy being one of the latter. This therapy involves applying pressure with the thumb to specific points, such as the san yin jiao (SP 6) and taichong (LR 3). The aim of this research was to assess the reduction in pain levels before and after the application of acupressure therapy on adolescent girls at SMKN 1 CIAMIS. The study employed a descriptive quantitative approach to illustrate the effects of acupressure therapy on dysmenorrhea in these students. A total of 93 respondents participated, with data collected directly using the Numeric Rating Scale (NRS) and following the standard operating procedure (SOP) for acupressure. The findings revealed that prior to acupressure therapy, nearly half of the adolescents (43%) experienced moderate pain, whereas post-therapy, a similar proportion (46%) reported only mild pain. The average pain score dropped from 6.76 before therapy to 2.6.